ANALISIS KECENDERUNGAN PENELITIAN TESIS MAHASISWA PADA PROGRAM STUDI MAGISTER PENDIDIKAN IPA UNIVERSITAS MATARAM - Lalu Zulkifli; Dwi Soelistya Dyah Jekti; Agus Ramdani (Postgraduate, University of Mataram, 2015)
This study aims to determine the distribution and trends of student thesis research on science education master study program University of Mataram, in terms of the type of research, the focus of study and research subjects. Data obtained through documentation techniques. Data were analyzed by descriptive qualitative tehniques and continued with FGD. The results showed that 73% of the student's thesis research themes included in the education and 27% belong to the natural science (Biology, Physics, and Chemistry). Education research was dominated by learning methods (50%), media applications and media development (17%), respectively, followed by the development of learning tools (13%) and the competence of teachers (3%). Thesis research subjects was dominated at the level of high school (70%), followed by junior high (25%), S1 (2.5%), and teachers (2.5%). Analysis based on the year thesis from 2009 to 2014 provided information that there were increasing trends on topics related to the development of media and the development of learning tools. Focus Group Discussion recommended that the topics for thesis research in the future which need to be improved are the topic of media development, development of learning tools and topics related aspects of critical thinking.Keywords: thesis research, trends, subjects, education